Business risk : financial reporting in Portugal and Spain - Alves, Maria Teresa (2022)
Disclosing iriformation about business risk is a quite relevant question. Companies, already, have to report about risk. Our objective is to acknowledge that disclosing such iriformation fol.fils important needs of financial iriformation users. We analyse the 2002 Annual Reports of companies integrating our samples, and make a content analyses. We observe that there is a statistical significant relation between disclosing operational, financial, strategic and business risks and size, when it concerns the Portuguese sample and between financial risk and leverage, when it concerns the Spanish sample. Yet, we found no evidence of relationship between financial disclosure and cost of debt